Recruitment Policy and Teachers' Job Performance in Kogi State Secondary Schools - Stephen, Olufemi Afolabi; Samuel , Onimisi Isaiah (International Journal of Educational Management, 2025)
This study adopted correlation research design to investigate one variable of managerial policies (recruitment) ) as it influences teachers' job performance in Kogi SI ale secondary schools. One research question and null hypothesis each was formulated to guide the study. There were 3,360 teachers in the existing 240 public secondary schools under the control of Kogi State Teaching Service Commission out of which 360 teachers were chosen using random sampling technique. The instrument used to elicit data was tagged Human Resource Management Policy Questionnaire (HRMP) validated by three lecturers from faculty of education, Kwara state University, Malete. Test re-test reliability method was used to obtain reliability co-efficient of 0. 726. The data Collected were analyzed using Mean and linear regression for research questions and hypotheses respectively at 0.05 level of significance. Teachers' recruitment policy was found to significantly influence teachers' job performance. I was found that teachers who were hired through normal recruitment procedure perform better. Therefore it was recommended, among others, that all teachers to be recruited should go through normal recruitment process while provision of efficient and effective working condition, good and timely payments of fringe benefits are sacrosanct for effective performance. The state government should ensure teachers enjoy family friendly policies which will go a long way to improve teachers job performance of in senior secondary schools.